The Simulation of Traffic Signal Preemption using GPS and Dijkstra Algorithm for Emergency Fire Handling at Makassar City Fire Service - Melki Friaswanto; Erick Alfons Lisangan; Sean Coonery Sumarta (Universitas Sanata Dharma, 2021)
The Makassar City Fire Department often faces obstacles in handling fires. Problems that often hinder such as congestion at crossroads, panic residents, and others. The result of this research is a system that can assist firefighters when handling fire cases in terms of accelerating the firefighting team to the location of the fire. Dijkstra's algorithm will be used to find the shortest path to the fire location and the travel time. Then the traffic signal preemption simulation adjusts the color of the lights when the GPS vehicle approaches the traffic lights on the path to be traversed. The simulation results show that the use of traffic signal preemption in collaboration with Dijkstra's algorithm and GPS can help the performance of the Makassar City Fire Department, especially for handling fires that require fast time.